CURAHAN WAKTU KERJA PEREMPUAN DALAM PROSES PEMBUATAN KOPRA DI KELURAHAN PANDU KECAMATAN BUNAKEN KOTA MANADO - Deiske Sasa Wangkanusa; Gene H. M. Kapantow; Theodora M. Katiandagho (Sam Ratulangi University, 2021)
This study aims to determine the time allocation of women in the copra-making process in Pandu Village, Bunaken Sub-district, Manado City. The research was conducted from November 2020 to January 2021. The data used were primary data and secondary data. Primary data was obtained through interviews using a questionnaire to 20 respondents, while secondary data was obtained from the Pandu Village Office. Furthermore, the data collected was analyzed descriptively. Based on the results of the study, it was found that the average time spent by women in Pandu Village, Bunaken District, Manado City in one copra-making process was 51.85 hours. Meanwhile, the work time for men was 71.20 hours. In other words, the time spent working for women in making copra was 42.14% of the total time spent working for men and women. The largest proportion of women's involvement is in the chopping sub-process which reaches 47.66%.